REKAYASA TANGKI MINI BERARUS (MINI FLUME TANK) UNTUK PENELITIAN TINGKAH LAKU RENANG IKAN - Wazir Mawardi; Ari Purbayanto; Daniel R. Monintja; Mulyono S. Baskoro; Budhi Hascaryo Iskandar (Institut Pertanian Bogor, 2011)
This research was carried out to construct mini flume tank that is reliable and ideal used for fish swimming behavior research through a series testing the flume tank technical performance. The mini flume tank has a maximum water velocity 85 cm/s (1.7 knots), with dimensions of 250 x 135 x 55 cm, and water capacity 155 litres. Based on observation, the field observation is clearly visible due to minimal air bubbles in the water velocity. Observations can be conducted from the two view fields (top and side) that allow observation of swimming endurance and fish tail flick easily. The water velocity is in laminar category at each level of the tested speeds.The rpm of engines is relatively stable for more than 200 minutes. Engine temperature is below 60 oC at frequency of 10 to 40 Hz. At frequency of 50 Hz the temperature reached 60 °C in 25 minutes and stable at 73oC after an hour. Water temperature changes during the test for more than 200 minutes at different speeds which have differences of 0.2 to 1.8 oC. The test result showed that the mini flume tank performance was reliable and ideal used for fish swimming behavior research.